Expression and Characterization of a Single-Chain Polypeptide Analogue of the Human Immunodeficiency Virus Type 1 gp120-CD4 Receptor Complex - Fouts, Timothy R. (American Society for Microbiology, 2000)
The infection of CD4(+) host cells by human immunodeficiency virus type 1 (HIV-1) is initiated by a temporal progression of interactions between specific cell surface receptors and the viral envelope protein, gp120. These interactions produce a number of intermediate structures with distinct conformational, functional, and antigenic features that may provide important targets for therapeutic and vaccination strategies against HIV infection. One such intermediate, the gp120-CD4 complex, arises from the interaction of gp120 with the CD4 receptor and enables interactions with specific coreceptors needed for viral entry. gp120-CD4 complexes are thus promising targets for anti-HIV vaccines and therapies. The development of such strategies would be greatly facilitated by a means to produce the gp120-CD4 complexes in a wide variety of contexts. Accordingly, we have developed single-chain polypeptide analogues that accurately replicate structural, functional, and antigenic features of the gp120-CD4 complex. One analogue (FLSC) consists of full-length HIV-1BaL gp120 and the D1D2 domains of CD4 joined by a 20-amino-acid linker. The second analogue (TcSC) contains a truncated form of the gp120 lacking portions of the C1, C5, V1, and V2 domains. Both molecules exhibited increased exposure of epitopes in the gp120 coreceptor-binding site but did not present epitopes of either gp120 or CD4 responsible for complex formation. Further, the FLSC and TcSC analogues bound specifically to CCR5 (R5) and blocked R5 virus infection. Thus, these single-chain chimeric molecules represent the first generation of soluble recombinant proteins that mimic the gp120-CD4 complex intermediate that arises during HIV replication.